2006
DOI: 10.1016/j.jcrc.2005.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial design—effect of prone positioning on clinical outcomes in infants and children with acute respiratory distress syndrome

Abstract: Purpose-This paper describes the methodology of an ongoing clinical trial of prone positioning in pediatric patients with acute lung injury (ALI). Nonrandomized studies suggest that prone positioning improves oxygenation in patients with ALI/ARDS without the risk of serious iatrogenic injury. It is not known if these improvements in oxygenation result in improvements in clinical outcomes. A clinical trial was needed to answer this question. Materials and Methods-The pediatric prone study is a multi-center, ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Of these citations and additional citations retrieved from other sources, we retrieved 50 studies for detailed evaluation and excluded 29. We selected 13 primary randomized and quasi-randomized trials for inclusion in our review and meta-analysis, [22][23][24][25][26][27][28][29][30][31][32][33][34] along with 8 citations providing duplicate or supplementary data (data from 4 of 13 primary trials were distributed among several additional publications) [35][36][37][38][39][40][41][42] ( Figure 1). Reviewers had perfect agreement on study inclusion.…”
Section: Literature Searchmentioning
confidence: 99%
“…Of these citations and additional citations retrieved from other sources, we retrieved 50 studies for detailed evaluation and excluded 29. We selected 13 primary randomized and quasi-randomized trials for inclusion in our review and meta-analysis, [22][23][24][25][26][27][28][29][30][31][32][33][34] along with 8 citations providing duplicate or supplementary data (data from 4 of 13 primary trials were distributed among several additional publications) [35][36][37][38][39][40][41][42] ( Figure 1). Reviewers had perfect agreement on study inclusion.…”
Section: Literature Searchmentioning
confidence: 99%
“…Many clinical case series have shown that prone position improves oxygenation in children [108][109][110][111][112][113][114][115][116][117][118]. Oxygenation improves within a short period (1-2 hours) after position change and can be sustained.…”
Section: Prone Positionmentioning
confidence: 99%
“…The primary reason for this eligibilityenrollment gap is parent or legal guardian refusal. 24 Parents are ethically entitled and legally empowered to make decisions on behalf of their children. 25 There is site-to-site variability in consent rates, based on PICU and investigatorspecific characteristics.…”
Section: Subject Enrollmentmentioning
confidence: 99%